Arqueología y género - Peytrequin Gómez, Jeffrey (2013)
This essay leads with some gender perspective`s aspects apply to Archaeology. As an example, it reviews topics like the past construction discursive manners; different ancient roles (male, female, childhood, elderly people, homosexuals) and their possible archaeological remains. In addition, it discuss women place in Archaeology`s history; making emphasis on Costa Rica`s professional life gender relationships.